Pengaruh Kemampuan Likuiditas Dan Struktur Modal Terhadap Kinerja Keuangan Pada PT. Gudang Garam, Tbk Periode 2014- 2023 - Arif Hidayat; Rosy Anggraini (Journal of Innovative and Creativity, 2026)
This study aims to determine the Effect of Liquidity Ability and Capital Structure on Financial Performance at PT Gudang Garam Tbk for the 2014-2023 Period. Liquidity is measured using the Current Ratio (CR) ratio, capital structure is measured using the Debt to Equity Ratio (DER), and financial performance is measured using the Return on Asset (ROA). This type of research is descriptive quantitative. The research population used in this study is the financial statements of PT Gudang Garam Tbk for the 10-year period 2014-2023. In this study, data analysis was used, namely Descriptive Statistics data analysis, Classical Assumption Test (Normality Test, Heteroscedasticity Test, Autocorrelation Test and Multicollinearity Test). Quantitative Analysis Test (Multiple Linear Regression, Determination Coefficient Analysis, Correlation Coefficient Analysis, and Hypothesis Test. Based on the results of the study partially using the t-test, Liquidity Ability has a significant effect on Financial Performance with a ttable > calculation value (4.553 > 2.365) with a significant value of 0.003 < 0.05, Capital Structure has a significant effect on Financial Performance with a ttable > calculation value (4.536 > 2.365) with a significant value of 0.003 < 0.05. The results of the simultaneous test for the influence of Liquidity Ability and Capital Structure on Financial Performance showed that there was a significant influence by obtaining a fcal of > ftable (10.928 > 4.74) with a significant value of 0.003 < 0.05. The results of the determination coefficient test showed an R Square (R²) value of 0.757 or 75.7% while the remaining 24.3% was influenced by other factors that were not studied by this study.